Advances in Engineering Design Select Proceedings of FLAME 2018 - Prasad, Anamika; Gupta, Shakti S.; Tyagi, R. K.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents select proceedings of the International Conference on Future Learning Aspects of Mechanical Engineering (FLAME 2018). The book covers mechanical design areas such as computational mechanics, finite element modeling, computer aided designing, tribology, fracture mechanics, and vibration. The book brings together different aspects of engineering design, and will be useful for researchers and professionals working in this field.
Static Analysis of Functionally Graded Plate Using Non-Linear Classical Plate Theory with Von-Karman Strains: A Complex Solution Analysis -- Modelling, Fabrication and Characterization of Kevlar Reinforced Composite -- Continum Damage Mechanics Based Simulation of Ductile Fracture of Cylindrical Tubes -- Improvement in Tribological Behaviour of Brake Pad Material with Cnt-Ni-P Composite Coating and Compare with Al2o3-Ni-P Composite Coating -- Experimental, Computational and Chemical Kinetic Analysis to Compare the Flame Structure of Methane-Air with Biogas-H2 -Air -- Design of Microfluidic Paper Based Device for the Detection of Nitrogen Dioxide in Atmosphere -- Assembly of Mechanical Parts in Virtual Environment -- Kinematic Synthesis of A Crossed Four-Bar Steering Linkage for Automobiles -- Design and Analysis of Reciprocating Screw for Injection Moulding Machine -- Static and Dynamic Characteristics of Two Lobe Hydrostatic Journal Bearing -- Integrated Topsis-Moora Model for Prioritization ofNew Bike Selection.-Shape Optimization of the Flywheel Using the Cubic B Spline Curve. .
Keywords: Engineering design; Computer-aided engineering; Manufactures; Multibody systems; Vibration; Mechanics, Applied; Engineering Design; Computer-Aided Engineering (CAD, CAE) and Design; Machines, Tools, Processes; Multibody Systems and Mechanical Vibrations